A concentric framework for leveraging big data for business value. (29th December 2020) - Chuang, Ta-Tao; Nakatani, Kazuo; Patil, Vivek H.
One focal area of big data research is to identify ways to create and reap business value from big data. Studies in this area have been based on one of three perspectives: architectural, strategical management and knowledge management. While these perspectives have academic and practical merits in isolation, they fail to integrate unique features of big data. To fill this void in the extant literature, we propose an integrated framework, which we call a concentric framework that differentiates value-adding factors of big data from those that affect technological requirements of a big data infrastructure. The concentric framework consists of three layers: explicit characteristics at the outer layer, implicit elements at the middle layer, and synergistic value in the core. We illustrate each layer of the framework using examples and identify tools and methods that can aid decision makers to use the framework for leveraging big data to create business value.